Preventive Effects of Escitalopram Against Anxiety-Like Depressive Behaviors in Monosodium Glutamate-Teated Rats Subjected to Partial Hepatectomy - Zhao, Bin-Bin; Chen, Lin-Lin; Long, Qing-Hua; Xie, Guang-Jing; Xu, Bo; Li, Ze-Fei; Wang, Ping; Li, Hanmin (Frontiers in Psychology, 2019)
The reasons for the relationship between depression and CLD are complex and multifactorial. Further research is needed to decipher the etiology and establish an optimal management approach for depression in these patients, including the potential role of nonpharmacological treatments. MSG-treated rats are more likely to develop anxiogenic- and depressive-like behaviors, which could be related to dysfunction of the serotonergic system. In the present study, we performed PH in MSG-treated rats and observed the histopathological changes in the OFC and liver. We also examined the effect of escitalopram, a widely used antidepressant, on liver regeneration and depression in this model. The MSG+PH-treated rats displayed decreased distances traveled in total, in the center arena, and in the left side of the arena in the inner OFT (as compared to saline, saline+PH, and MSG-treated animals). The present study established that PH aggravated depression in MSG-treated rats, concordant with damaged Nissl bodies (and neurites), decreased IBA-1 and Sox-2 expression in the OFC and neurotransmitter disorder. Escitalopram treatment could alleviate these pathological changes as well as reduce hepatic steatosis and lipid metabolism.